2007
DOI: 10.1111/j.1365-2303.2007.00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative cytology (squash smear) in neurosurgical practice – pitfalls in diagnosis experience based on 3057 samples from a single institution

Abstract: This is the largest series reported from India to the best of our knowledge. Squash smear technique is a very reliable and rapid method of intraoperative diagnosis. Knowledge of clinical and neuroimaging details helps the experienced neuropathologist to improve the diagnostic accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 9 publications
5
55
1
2
Order By: Relevance
“…neoplastic lesions [table/ Fig-1 Fig-3] have shown the importance of squash cytology for offering intra-operative diagnosis of intracranial lesions [7][8][9][10]. In the present study, however, we have shown that using squash cytology as standalone diagnostic procedure, it is possible to achieve consistently high sensitivity and specificity for intra- *time interval between removal of mass from the body till intra-operative diagnosis given to surgeon operative diagnosis of intracranial lesions even in resource-limited setting where frozen section facility is not available.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…neoplastic lesions [table/ Fig-1 Fig-3] have shown the importance of squash cytology for offering intra-operative diagnosis of intracranial lesions [7][8][9][10]. In the present study, however, we have shown that using squash cytology as standalone diagnostic procedure, it is possible to achieve consistently high sensitivity and specificity for intra- *time interval between removal of mass from the body till intra-operative diagnosis given to surgeon operative diagnosis of intracranial lesions even in resource-limited setting where frozen section facility is not available.…”
Section: Resultsmentioning
confidence: 99%
“…As suggested by Powell et al, a squash cytology prepared with good amount of tissue is enriched with good cytological and histological details and a pathologist get benefits of both cytology as well as histology [20]. The cell type with differentiation of nuclear and cytoplasmic features of neurons, oligodeandroglial cells and astrocytes are well appreciated with this technique [8,20].…”
Section: Resultsmentioning
confidence: 99%
“…Toluidine blue method that we have used in our study was introduced by Russel et al 1 Goel et al 2 had also used toluidine blue in their study. In this method, smears prepared were fixed with absolute methanol for 1 min, stained with toluidine blue for 1 min, rinsed in tap water and then dried on the hot plate, cleared in xylene, and mounted in DPX.…”
Section: Methodsmentioning
confidence: 98%
“…Intraoperative examination can guide the neurosurgeon in selecting the appropriate surgical management [1-3]. Ideally, the examination should be accurate, fast, and allow tissue preservation for further study in paraffin [4-6]. The most commonly used techniques are squash and frozen section (FS) [6, 7].…”
Section: Introductionmentioning
confidence: 99%